The Compliment Strategies Used by the Native Speakers in Teaching the EFL Learners at De Access Hotel and Culinary Training Centre - Wiratmoko, Gandung Aulia (PT Inovasi Pratama Internasional, 2023)
This study aimed on elaborating the compliment strategies done by the native speakers in teaching English as foreign language students. The writer applied descriptive research design which applied the participant observation method with passive observer. The population of the research was the students of De Access Hotel And Culinary Training Centre with 172 students and divided into 7 groups and the samples are group 3 and 6 consisted of 50 students. The researcher found four compliment functions used by the native speakers, namely expressing admiration, solidarity, conversation strategy and reinforced desired behavior.